Kajian Penerapan Konsep Konstruksi Ramping di Palembang - Ilham Fazri; Yani Rahmawati (Arsir: Jurnal Arsitektur, 2024)
This research investigates the implementation of lean construction and its benefits in construction projects in Palembang. A qualitative approach is applied through literature review and in-depth interviews with respondents experienced in the construction projects. The interview results indicate that the implementation of lean construction in Palembang is still limited, although it has the potential to reduce carbon emissions and improve efficiency. Additionally, it is found that further introduction to the concept of lean construction is highly necessary, especially among architects, to facilitate the decision-making for sustainable design. The development of awareness of lean construction to practitioners in the architecture, engineering, and construction (AEC) industry in Palembang is essential to support the realisation of sustainable development.